Knowledge about Autism Spectrum Disorder (ASD) predicts motivation to volunteer : a cross-sectional survey among psychology students - Jocelyn Deana Jominol,; Ching, Sin Siau; Rabbani, Mohtaram; Mimi Fitriana,; Mansour Amini,; Amira Najiha Yahya,; Jing, Ni Tee; Muhamad Nur Fariduddin, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Children with Autism Spectrum Disorder (ASD) and their parents require support from the community, and could profit from volunteer work involving the family. At the same time, university students demonstrate a high willingness to volunteer in community initiatives such as work involving children with ASD. This study aims to examine the relationship between ASD knowledge and the motivation to volunteer among university students. Students (N=150) from a private university in the Klang Valley, Malaysia, participated in this study. Instruments utilized in this study were the Stone Autism Survey and Volunteer Functions Inventory. The results indicated that a higher level of ASD knowledge was the strongest predictor of higher motivation to volunteer after adjusting for relevant demographic factors and exposure to ASD children. Meanwhile, female and Hindu participants reported a significantly higher motivation to volunteer. This study emphasizes the need to increase factual knowledge about ASD among university students, and any effort to encourage students to volunteer in helping individuals with ASD should include knowledge sharing about this population.